New venture creation entrepreneurship for the 21st century - Timmons, Jeffry A.; Spinelli, Stephen Jr (McGraw Hill, 2009)
Timmons and Spinelli cover the process of getting a new venture started, growing the venture, and successfully harvesting it. Through text, case studies, and hands-on exercises, this how-to text guides students in discovering the concepts of entrepreneurship and the competencies, skills, tools, and experience to equip students to successfully launch a new venture and recognize entrepreneurial opportunities.